Improved Artificial Potential Field Method for Dual-manipulator Path Planning Algorithm - Haonan Ma; Zhian Zhang; Qingliang Li (Jixie chuandong, 2021)
Aiming at the problem that the traditional artificial potential field method cannot constrain the overall posture of the dual manipulator system when planning the path of the dual manipulator system，and it is easy to fall into the local extreme point，the artificial potential field method is improved. Use the D-H method to analyze the kinematics of the dual-manipulator system，use the cylindrical-hemisphere bounding box model as the collision detection model. The construction of a new potential energy function dual-manipulator system is used to plan the path，use the method of constructing virtual target points to help the manipulator escape local extreme points. Simulation experiments show that the improved algorithm overcomes the shortcomings of local minima and realizes the path planning of the dual-manipulator system.